Parliamentary Oversight of International Loan Agreements and Related Processes - Inter-Parliamentary Union; World Bank; Inter-Parliamentary Union; World Bank (2013)
The study indicates that there is plenty of room for parliaments to exert influence in the loan approval process by instituting legal frameworks or by strengthening existing ones, as well as by improving a number of oversight practices. A common thread throughout the study is that these legal frameworks are often un-derutilized.